Reducing stigma toward mental illness and substance use issues in primary health care in Chile: Protocol of a cluster controlled trial study - Sapag, Jaime C.; Traub, Carolina; Velasco, Paola R.; Arratia, Tamara; Alvarado, Rubén; Aracena, Marcela; Poblete, Fernando C.; Villarroel, Luis; Bravo, Paulina; Álvarez-Huenchulaf, Cinthia; Jofré Escalona, Ana; Vargas-Malebrán, Nelson; et al. (Frontiers in Psychiatry, 2022)
Primary Health Care (PHC) has great potential to early detection and provision of accessible and coordinated services to people who present mental illness and/or substance use issues (MISUI). However, stigma toward people with MISUI among PHC professionals is a significant barrier to accessing quality of care. This research project main goal is to determine the effectiveness of a comprehensive anti-stigma intervention in reducing stigmatizing attitudes and behaviours among Chilean PHC providers toward individuals with MISUI. The intervention is based on a culturally adapted initiative that was previously developed in Canada and then pilot-tested in Peru. The 18-month intervention includes five components that are simultaneously implemented: (1) Develop a Team of Local Champions in each intervention CESFAM; (2) Analysis of Internal CESFAM Policies, Procedures, and Protocols to determine areas of improvement (3) Raising Awareness of stigma toward MISUI using various forms of media within the CESFAM; (4) Innovative Contact-Based Education workshops on anti-stigma and recovery principles; and (5) Recovery-Based Arts, a multi-week arts workshop for PHC providers and users to produce artwork related to MISUI and recovery. The expected intervention outcomes are the following: Participation in the experimental group will result in a significant decrease in stigmatising attitudes among PHC providers towards individuals with MISUI compared with the control group; Participation in the experimental group will result in a significant decrease of PHC users experiences of stigma conveyed by PHC providers compared with the control group; The changes in attitudes and behaviours within the experimental group will be sustained over time as measured at 6 months-follow-up. To evaluate the effectiveness of this 18-month intervention, a 4-year, two-arm, cluster-randomised controlled trial is proposed, with CESFAMs being the unit of randomization (or “cluster”). Implementation Science approach will be taken to measure relevant implementation outcomes for each component of the intervention, and through qualitative data collection with CESFAM providers and authorities. Data analysis will be carried out using SAS 9.4 and R 3.5. Mixed-effect modelling will be used for both PHC provider and user data, which will include individuals and CESFAM as random effects and group (intervention/control) as fixed effects.